Cardiac Ventricle Laceration in a Battered Child: A Case Report (Medico Legal Update, 2020)
Cardiac laceration in child abuse cases is uncommon. Very few case studies are available illustrating theleft ventricular rupture following blunt chest injuries. This article presents a case of sudden death of a twoand a half year-old female child brought with history of fall on level ground while playing. The autopsyrevealed multiple types of injuries over the whole body with duration varying from less than a day to morethan 6 months old. Left ventricular rupture and liver laceration were the primary injuries contributing todeath. Child abuse cases should never be examined with a preconception of finding the classical features ofintracranial hematomas.